Pemberdayaan Ekonomi Masyarakat Desa dengan Pelatihan Keterampilan Web Digital Membangun Kemandirian dan Akses Pekerjaan di Kecamatan Cikarang Utara - Andi Pratama; Siti Rahmawati (Journal of Community Action, 2025)
Economic empowerment of village communities is one of the efforts to improve people's standard of living and independence in the digital era. This research aims to analyze the effect of digital web skills training on community economic empowerment in North Cikarang District. This training program aims to improve people's abilities in utilizing information technology, especially skills in creating and managing websites. The method used in this research is a quantitative approach with descriptive data analysis techniques. The research results show that digital web skills training can increase job access, expand business opportunities, and create economic independence for village communities. This training has a positive impact in improving participants' technical skills and digital knowledge, which in turn can improve their quality of life. In addition, this training opens up new job opportunities in the digital sector, such as website creation and online marketing. Overall, this training program plays an important role in supporting economic empowerment and improving the welfare of village communities, especially in North Cikarang District.